CaCO3-coated ZnO core-shell structure composite powder and preparation method thereof
By controlling the pH value and adding zinc salt and carbonate in the carbonation reaction, CaCO3@ZnO core-shell structure composite powder was prepared, which solved the problems of poor dispersion and low whiteness, and achieved efficient and environmentally friendly composite powder preparation, which was suitable for high-end rubber, plastic and other fields.
Patent Information
- Application Number
- CN202411697567.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-11
AI Technical Summary
The CaCO3@ZnO core-shell structure composite powder prepared in the prior art has problems of poor dispersion and low whiteness, and it is difficult to apply in high-end rubber, plastic and other fields.
The CaCO3@ZnO core-shell structure composite powder was prepared by combining carbonation and precipitation. The pH value of the system was controlled to be 8.0-9.0 in the initial stage of the carbonation reaction, and soluble zinc salts and soluble carbonates were added to make ZnCO3 precipitation deposited on the surface of cubic or spherical nano calcium carbonate after fracture and coated.
The uniform coating of zinc oxide is achieved, and the dispersion and whiteness of the composite powder is improved. The whiteness is greater than 95 and the zinc oxide content is low (5% to 15%). It has good application effects in rubber, achieving the purpose of low cost, high efficiency and environmental protection.
Smart Images

Figure CN119591140A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of calcium carbonate preparation, and in particular to a CaCO3@ZnO core-shell structure composite powder and a preparation method thereof. Technical Background
[0002] As the "food" of modern industry, mineral resources play a vital role in the development of modern industry. Carbonate minerals are one of the most valuable mineral resources for industrial applications. They occupy a very important position in my country's industrial system, especially the mining and application of calcium carbonate. Calcium carbonate is an inorganic compound composed of three different elements: C, O, and Ca. Its molecular formula is CaCO3. It has stable physical and chemical properties and is the main component of limestone, calcite, marble, dolomite, chalk, coral and shells. my country's calcium carbonate resources are mainly distributed in North China, Sichuan, Anhui, Yunnan, Guangxi, Guizhou and other regions. They are widely distributed and have abundant reserves. Calcium carbonate is widely used in industrial production because of its excellent and unique physical and chemical properties, wide sources and low prices. In particular, heavy calcium carbonate and light (nano) calcium carbonate products with high added value are widely used in rubber, plastics, papermaking, coatings and other industries. With the rapid development of papermaking, coatings, plastics, rubber and other material industries, the market demand for calcium carbonate products is increasing, and the production and consumption of calcium carbonate are showing a rapid growth trend. The current competition in calcium carbonate products is mainly concentrated in the fields of light calcium carbonate and nano calcium carbonate. Surface-modified nano calcium carbonate, as one of the products with the highest technological content among nano calcium carbonate products, is the focus of industrial layout in various countries.
[0003] Zinc oxide is a white powder with the chemical formula ZnO. It is an important branch of the inorganic chemical zinc salt series. It is an important basic chemical raw material and new material that is indispensable in the national economic construction. It is widely used in ceramics, electronics, medicine, chemicals, rubber, coatings, textiles and other fields. my country's zinc oxide market is huge, and the demand for zinc oxide is showing a steady growth trend. Rubber is the largest demand area for downstream applications of zinc oxide, accounting for about 60%, and is one of the main driving forces for the development of the zinc oxide industry. At present, there is no product that can completely replace zinc oxide for rubber. In the next few years, the rubber industry will still be the largest demand area for downstream zinc oxide. However, the zinc oxide industry is a resource-consuming industry. During the production of zinc oxide, a large amount of wastewater, waste gas, and waste residue are generated while consuming a large amount of zinc resources, causing environmental pollution. Under the multiple challenges of resource shortages, environmental pressures and rising production costs, taking a low-zinc, high-efficiency, energy-saving and environmentally friendly route is an inevitable trend in the development of the zinc oxide industry.
[0004] Studies have shown that constructing a zinc oxide-coated calcium carbonate (CaCO3@ZnO) core-shell structure composite material with calcium carbonate as the core and nano-zinc oxide as the shell can not only reduce production costs, increase the added value of calcium carbonate, and make calcium carbonate a high-end product, but also play the same role as solid ZnO particles, achieving the goals of environmental protection, zinc reduction, and high efficiency.
[0005] Patent CN117342594A discloses a method for preparing a core-shell calcium carbonate with anti-ultraviolet properties. The sol-gel method is used to prepare CaCO3@ZnO core-shell composite powders using alkali metal hydroxides and zinc salts as raw materials. The method is simple in process and can obtain a core-shell product with a calcium carbonate surface completely and evenly coated with nano zinc oxide. The coating effect is good, the product has a regular morphology, good dispersibility, high whiteness, and excellent anti-ultraviolet properties. When the coating amount of nano zinc oxide reaches 20%, the ultraviolet absorption intensity of the prepared CaCO3@ZnO core-shell structure can achieve the same effect as pure nano ZnO. However, the method uses anhydrous ethanol, methanol and other solutions as reaction reagents, and the production cost is high, making it difficult to achieve industrial production.
[0006] Huang Xincheng et al. used the liquid phase precipitation method to generate hydroxyapatite on the surface of CaCO3 to deposit Zn 2+ The ZnO / CaCO3 composite powder was prepared by assembling ZnO and CaCO3 together through the adsorption effect. When the composite ratio of ZnO and CaCO3 was 1:2 and calcined at 300-350℃, the composite powder was applied to styrene-butadiene rubber. Under the same proportion, the composite powder had a faster vulcanization rate, up to 0.247s. -1 , the actual use of ZnO is small, and it has a good economic prospect. The ZnO / CaCO3 composite powder prepared by this method is micron-sized, while nano-sized zinc oxide fillers are used in high-end rubber, plastic and other products; in addition, the ZnO particles in this method are adsorbed on the surface of calcium carbonate, and the affinity between ZnO and calcium carbonate is poor, and the ZnO particles are easy to fall off, resulting in poor coating effect (Huang Xincheng, Chen Xuemei; Preparation of ZnO / CaCO3 composite materials and their application in styrene-butadiene rubber vulcanization [J]. Journal of Materials Science and Engineering, 1673-2812 (2022) 01-0070-07).
[0007] Chinese patent CN106279762A discloses an ammonia-based preparation method for core-shell zinc oxide powder, which uses calcium carbonate as a template, controls the reaction temperature to slowly grow zinc carbonate on the surface of calcium carbonate, and finally obtains core-shell zinc oxide powder coated with flaky zinc oxide on the surface of calcium carbonate after calcination. The prepared core-shell zinc oxide powder has good dispersibility and processability in vulcanized rubber, and can fully promote rubber vulcanization and improve the tensile strength, elongation and tear strength of rubber while maintaining good sulfur change data. However, the particle size of the core-shell zinc oxide powder is between 2 and 15 μm, which belongs to micron materials and cannot be used in high-end rubber, plastic and other products. In addition, the weight ratio of Zn / Ca in the Fang Ming method is between 2 / 8 and 7 / 3, the amount of ZnO used is large, and a large amount of ammonia and ammonium bicarbonate are used, which is not friendly to the environment and cannot achieve the purposes of low zinc, high efficiency and environmental protection.
[0008] Chinese patent CN106752106B discloses a high-brightness white anti-ultraviolet and anti-aging functional filler nano calcium carbonate and its preparation method and use. At the end of the preparation of nano calcium carbonate, the concentration of the reaction system, the termination pH value, the reaction temperature, the formula of the dispersant and the selection of the coating agent are precisely controlled to obtain a high-performance multi-purpose nano calcium carbonate with a particle size of 80nm-200nm, a whiteness of more than 92, a zinc oxide coating of 4%, no agglomeration, and anti-ultraviolet and anti-aging properties. However, the nano calcium carbonate prepared by this method has a low whiteness, which affects the quality of calcium carbonate and cannot meet the requirements of high-quality calcium carbonate.
[0009] Chinese patent CN101412818A discloses an industrial preparation method of nano calcium carbonate for antibacterial and mildew-proof silicone rubber, wherein silicate and zinc salt are added to the carbonized nano calcium carbonate slurry, kiln gas is introduced and a certain reaction temperature is controlled, and under the synergistic effect of the two components of silicate and zinc salt, they are hydrolyzed into silica sol and zinc hydroxide respectively, which are uniformly coated on the surface of nano calcium carbonate, forming a nano calcium carbonate with a core-shell structure having a layer of weather-resistant silicon dioxide and a nano zinc oxide shell uniformly coated on the surface. The product can be used as a functional filler for silicone rubber, having good thixotropy and having both antibacterial and mildew-proof functions and weather resistance. However, the maximum whiteness value of the product is only 93, and to be used as high-quality calcium carbonate, it is still necessary to further improve the production technology and improve the whiteness of the product.
[0010] Chinese patent CN113000058A discloses a method for preparing and applying a nano zinc oxide / calcium carbonate composite powder, using an in-situ chemical composite method and a mechanical composite method to prepare a nano zinc oxide / calcium carbonate composite. The prepared product can be used in rubber as an auxiliary agent for rubber vulcanization to improve the physical properties of rubber such as tensile strength and elongation. Under visible light, the product also exhibits photocatalytic activity that is superior to that of pure nano zinc oxide. However, due to the poor affinity between zinc oxide and calcium carbonate, it is difficult to uniformly coat zinc oxide on the surface of calcium carbonate only by a simple in-situ chemical composite method or a mechanical composite method, resulting in poor interface bonding between composite particles, low stability, and easy detachment of ZnO, thereby affecting the overall performance of the product.
[0011] Chinese patent CN111606351B discloses a nano material of zinc oxide coated calcium carbonate and its preparation method, with nano calcium carbonate particles as core and urea as precipitant, firstly using hydrothermal method to prepare CaCO3@Zn(OH)2 under high temperature and high pressure, and then calcining at high temperature to obtain CaCO3@ZnO core-shell structure composite nanoparticles. The surface of the obtained CaCO3@ZnO core-shell structure composite nanoparticle calcium carbonate is completely covered with flaky zinc oxide, and the coating effect is good. However, the CaCO3@ZnO core-shell structure composite nanoparticles prepared by the invention method have poor dispersibility, and the particles are easy to adhere to form clusters; in addition, the method uses urea as a precipitant, the reaction is slow, the preparation cycle is long, the energy consumption is high, and the reactants need to be placed in a sealed high temperature and high pressure reaction vessel, and the operating conditions are relatively harsh, resulting in difficulties in large-scale production.
[0012] The CaCO3@ZnO core-shell structure material prepared by the above disclosed process has the limitations of low powder whiteness and poor dispersibility. Therefore, it is an important direction for the development of the entire calcium carbonate industry and the zinc oxide industry to study and develop a composite powder that effectively combines CaCO3 and ZnO, so that it has the performance of zinc oxide, achieves the goals of low zinc, high efficiency, and environmental protection, and at the same time increases the added value of nano calcium carbonate, making nano calcium a high-end product. Summary of the invention
[0013] In view of the above problems, the present invention provides a CaCO3@ZnO core-shell structure composite powder to solve the problems of poor dispersibility and low whiteness of the CaCO3@ZnO core-shell structure composite powder prepared by the prior art.
[0014] To achieve the above object, the present invention adopts the following technical solution:
[0015] A CaCO3@ZnO core-shell structure composite powder, comprising a nano calcium carbonate core and a zinc oxide shell coated on the surface of the core; in the CaCO3@ZnO core-shell structure composite powder, the weight of zinc oxide is 5% to 15% of the weight of the nano calcium carbonate.
[0016] Preferably, in the CaCO3@ZnO core-shell structure composite powder, the weight of zinc oxide is 10% to 15% of the weight of nano-calcium carbonate.
[0017] Preferably, in the CaCO3@ZnO core-shell structure composite powder, zinc oxide is deposited on the surface of calcium carbonate in the form of particles, and the particle size thereof is 10 to 20 nm.
[0018] Preferably, in the CaCO3@ZnO core-shell structure composite powder, the particle size of zinc oxide is 10 to 15 nm.
[0019] Preferably, the CaCO3@ZnO core-shell structure composite powder further contains stearic acid, and the stearic acid is coated on the outer surface of the CaCO3@ZnO core-shell structure composite powder.
[0020] Preferably, the method for preparing the CaCO3@ZnO core-shell structure composite powder comprises the following steps:
[0021] (1) preparing a calcium hydroxide slurry, and then introducing a mixed gas containing carbon dioxide into the slurry to cause a carbonation reaction. When the pH value of the system is 8.0 to 9.0, adding a soluble zinc salt and a soluble carbonate into the system, stirring and reacting, and obtaining a mixed slurry;
[0022] (2) removing impurities and moisture from the mixed slurry obtained in step (1) to obtain CaCO3@ZnCO3 powder;
[0023] (3) The CaCO3@ZnCO3 powder obtained in step (2) is calcined to obtain a CaCO3@ZnO core-shell structure composite powder.
[0024] Preferably, in step (1), the solid content of calcium hydroxide in the calcium hydroxide slurry is 8.0 to 15.0%.
[0025] Preferably, in step (1), the temperature of the carbonation reaction is 18 to 25° C., and the flow rate of the mixed gas containing carbon dioxide is 1 to 4 m / s. 3 / h, the volume concentration of carbon dioxide is 15-25%.
[0026] Preferably, in step (1), the stirring speed is 800 to 1200 r / min.
[0027] Preferably, in step (1), the soluble zinc salt is one of zinc acetate dihydrate, zinc citrate, zinc chloride, zinc sulfate, and zinc nitrate; and the soluble carbonate is one of sodium carbonate, potassium carbonate, ammonium carbonate, and ammonium bicarbonate.
[0028] Preferably, the amount of the soluble zinc salt added is calculated based on the weight of the generated ZnO being 5% to 15% of the weight of the nano-calcium carbonate; the amount of the soluble carbonate added is calculated based on the amount that can just react completely with the soluble zinc salt.
[0029] Preferably, in step (1), the pH value of the system is regulated to be 7.0-8.5 during stirring.
[0030] Preferably, the stirring time is 2 to 4 hours.
[0031] Preferably, an acid or a base is added as a pH adjuster to adjust the pH value of the system.
[0032] Preferably, the acid is hydrochloric acid, and the base is one of sodium hydroxide and potassium hydroxide, and the concentration of both is 0.1-1.0 mol / L.
[0033] Preferably, the method of removing impurities and moisture in step (2) is filter pressing and drying.
[0034] Preferably, the drying method is: drying in a blast drying oven, the drying temperature is 110 to 150° C., and the drying time is 12 to 24 hours.
[0035] Preferably, in step (3), the heating rate of calcination is 3-10°C / min, and the temperature is raised to 300-450°C and then kept at this temperature for 1-5 hours.
[0036] Preferably, in step (3), the CaCO3@ZnO core-shell structure composite powder is surface modified using stearic acid as a modifier, the amount of stearic acid used is 3.0-4.0% of the weight of the nano-calcium carbonate; the modification temperature is 90-95°C, and the time is 30-60 min.
[0037] Preferably, the surface modification treatment is carried out in a high-speed mixer.
[0038] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0039] (1) The CaCO3@ZnO core-shell structure composite powder of the present invention has uniform zinc oxide coating, good dispersibility, and a whiteness greater than 95. In addition, the zinc oxide content in the composite powder is very low, only 5% to 15% of the weight of nano-calcium carbonate, but has a good application effect in rubber, especially when the zinc oxide content is 10% to 15% of the weight of nano-calcium carbonate, it can exert an application effect equivalent to that of nano-zinc oxide, achieving the goals of low cost, high efficiency, and environmental protection.
[0040] (2) The preparation method of the present invention combines the carbonation method with the precipitation method. In the initial stage of the carbonation reaction, a linear intermediate of nano-calcium carbonate is mainly generated. As the reaction time proceeds, the linear intermediate grows continuously. At the end of the reaction, the linear intermediate will instantly break and become a cubic or spherical nano-calcium carbonate. When the pH value of the carbonation system reaches 8.0 to 9.0, it is very close to the end of the reaction. The present invention selects to add zinc salt and carbonate to react at this pH value, that is, before the linear intermediate breaks, so that the generated ZnCO3 precipitates and deposits on the surface of the cubic or spherical nano-calcium carbonate after the break and coats it, preventing the nanoparticles after the break from agglomerating due to the higher specific surface energy, thereby obtaining a CaCO3@ZnO core-shell structure composite powder material with good dispersibility.
[0041] (3) In order to make ZnO evenly distributed on the surface of nano-calcium carbonate and obtain a CaCO3@ZnO core-shell structure composite powder with good coating effect, during the process of ZnCO3 coating nano-calcium carbonate, the present invention can regulate the surface charge between nano-calcium carbonate and ZnCO3 by regulating the pH value of the reaction system within the range of 7.0 to 8.5, thereby increasing the binding energy between them, so that ZnCO3 is more evenly coated on the surface of nano-calcium carbonate, thereby achieving effective control of the coating layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 Scanning electron microscope image of CaCO3@ZnO core-shell structure composite powder prepared by treatment 1;
[0043] Figure 2 Scanning electron microscope image of CaCO3@ZnO core-shell structure composite powder prepared for treatment 2;
[0044] Figure 3 Scanning electron microscope image of CaCO3@ZnO core-shell structure composite powder prepared for treatment 3;
[0045] Figure 5 Scanning electron microscope image of CaCO3@ZnO core-shell structure composite powder prepared for treatment 4;
[0046] Figure 4 Scanning electron microscope image of CaCO3@ZnO core-shell structure composite powder prepared by treatment 5;
[0047] Figure 6 Scanning electron microscope image of CaCO3@ZnO core-shell structure composite powder prepared for treatment 6;
[0048] Figure 7 Scanning electron microscope image of CaCO3@ZnO core-shell structure composite powder prepared for treatment 7;
[0049] Figure 8 Scanning electron microscope image of CaCO3@ZnO core-shell structure composite powder prepared by treatment 8;
[0050] Fig. 9 Scanning electron microscope image of CaCO3@ZnO core-shell structure composite powder prepared for treatment 9;
[0051] Fig.10 Scanning electron microscope image of CaCO3@ZnO core-shell structure composite powder prepared by treatment 10;
[0052] Fig.11 This is a scanning electron microscope image of the commercially available nano zinc oxide purchased in Comparative Example 1;
[0053] Fig.12 This is a scanning electron microscope image of the CaCO3@ZnO core-shell structure composite powder prepared in Comparative Example 2;
[0054] Fig.13 This is a scanning electron microscope image of the CaCO3@ZnO core-shell structure composite powder prepared in Comparative Example 3. DETAILED DESCRIPTION
[0055] In order to better present the present invention, it is illustrated by specific implementation cases, which belong to the protection scope of the present invention but do not limit the protection scope of the present invention.
[0056] Example 1
[0057] A method for preparing a CaCO3@ZnO core-shell structure composite powder comprises the following steps:
[0058] (1) Calcium hydroxide slurry with a solid content of 8.0-15.0% is prepared and pumped into a carbonization tower, and carbon dioxide with a volume concentration of 15-25% and a flow rate of 1-4 m / s is introduced at a temperature of 18-25° C. and a stirring speed of 800-1200 r / min. 3 / h of carbon dioxide and air mixed gas, so that calcium hydroxide reacts with carbon dioxide to generate CaCO3; when the carbonation reaction is carried out to the pH value of the system is 8.0-9.0, a soluble zinc salt and a soluble carbonate are added, and the amount of the soluble zinc salt added is calculated based on the weight of the generated ZnO being 5-15% of the weight of the nano calcium carbonate, and the amount of the soluble carbonate added is calculated just to make the soluble zinc salt react completely, and stirred for 2-4 hours to make the soluble zinc salt and the soluble carbonate fully react to generate ZnCO3 coated on the surface of CaCO3 to obtain a mixed slurry;
[0059] (2) After filtering the mixed slurry of step (1), drying it in a forced air drying oven at 110-150° C. for 12-24 h to obtain CaCO3@ZnCO3 powder;
[0060] (3) The CaCO3@ZnCO3 powder obtained in step (2) is placed in a muffle furnace, the heating rate is set to 3-10°C / min, the temperature is raised to 300-450°C and then kept warm for 1-5 hours to obtain a CaCO3@ZnO core-shell-structured composite powder of zinc oxide-coated nano-calcium carbonate.
[0061] In this embodiment, referring to the preparation method of the CaCO3@ZnO core-shell structure composite powder provided above, different treatment groups (as shown in Table 1) were set up with the added soluble zinc salt and soluble carbonate combination and the pH value of the node system as variables to investigate the effect of adding different soluble zinc salt and soluble carbonate combinations on product performance at different system pH values during the carbonation reaction.
[0062] Table 1 The settings of each treatment group in Example 1
[0063] Group Combination of soluble zinc salt and soluble carbonate pH value of the node system Process 1 Zinc nitrate + ammonium carbonate 8.0 Process 2 Zinc chloride and sodium carbonate 8.5 Process 3 Zinc Citrate and Potassium Carbonate 9.0 Process 4 Zinc chloride and sodium carbonate 9.5 Process 5 Zinc chloride and sodium carbonate 7.5
[0064] Example 2
[0065] A method for preparing a CaCO3@ZnO core-shell structure composite powder comprises the following steps:
[0066] (1) The quicklime is digested to form a calcium hydroxide slurry with a solid content of 8.0-15.0%, which is then pumped into a carbonization tower. At a temperature of 18-25° C. and a stirring speed of 800-1200 r / min, carbon dioxide with a volume concentration of 15-25% and a flow rate of 1-4 m 3 / h of carbon dioxide and air; when the carbonation reaction is carried out to a pH value of 8.0-9.0, the introduction of the mixed gas is stopped, and a soluble zinc salt and a soluble carbonate are added, the amount of the soluble zinc salt added is calculated based on the weight of the generated ZnO being 5-15% of the weight of the nano-calcium carbonate, and the amount of the soluble carbonate added is calculated just to make the soluble zinc salt react completely, stirring for 2-4 hours, and adding an acid or a base as a pH value adjuster during the stirring process to adjust the pH value of the system to 7.0-8.5, to obtain a mixed slurry; the acid added is hydrochloric acid, or the base added is one of sodium hydroxide and potassium hydroxide, and the concentration is 0.1-1.0 mol / L;
[0067] (2) filtering the mixed slurry of step (1) and drying it in a forced air drying oven at 110 to 150° C. for 12 to 24 hours to obtain CaCO3@ZnCO3 powder;
[0068] (3) The CaCO3@ZnCO3 powder obtained in step (2) is placed in a muffle furnace, the heating rate is set to 3-10°C / min, the temperature is raised to 300-450°C and then kept warm for 1-5 hours to obtain a CaCO3@ZnO core-shell-structured composite powder of zinc oxide-coated nano-calcium carbonate.
[0069] In this embodiment, referring to the preparation method of the CaCO3@ZnO core-shell structure composite powder provided above, the same combination of soluble zinc salt and soluble carbonate as treatment groups 1 to 3 in Example 1 and the pH value of the node system were selected, and the type of pH regulator added and the pH value of the system regulated were used as variables to set different treatment groups (as shown in Table 2) to examine the effect of regulating different system pH values on product performance.
[0070] Table 2 The settings of each treatment group in Example 2
[0071]
[0072] Example 3
[0073] The CaCO3@ZnO core-shell structure composite powder prepared by treatments 1 to 3 of Example 1 is placed in a high-speed mixer, and the composite powder is surface-modified using stearic acid as a modifier, with the amount of stearic acid being 3.0 to 4.0% of the weight of the nano-calcium carbonate; the modification temperature is 90 to 95°C, and the time is 30 to 60 min.
[0074] In this example, referring to the preparation method of the CaCO3@ZnO core-shell structure composite powder provided above, different treatment groups (as shown in Table 3) were set with modification temperature, modification time and amount of stearic acid as variables, and compared with the products prepared by treatments 1 to 3 in Example 1 to examine the effect of modification on product performance.
[0075] Table 3 The settings of each treatment group in Example 3
[0076] Group Modification temperature / ℃ Modification time / min Amount of stearic acid / % Process 11 90 60 3.0 Processing 12 92 50 3.5 Process 13 95 30 4.0
[0077] Example 4
[0078] The CaCO3@ZnO core-shell structure composite powder prepared by treatments 6 to 8 of Example 2 is placed in a high-speed mixer, and the composite powder is surface-modified using stearic acid as a modifier, with the amount of stearic acid being 3.0 to 4.0% of the weight of the nano-calcium carbonate; the modification temperature is 90 to 95°C, and the time is 30 to 60 min.
[0079] In this example, referring to the preparation method of the CaCO3@ZnO core-shell structure composite powder provided above, different treatment groups (as shown in Table 3) were set with modification temperature, modification time and amount of stearic acid as variables, and compared with the products prepared by treatments 6 to 8 in Example 2 to examine the effect of modification on product performance.
[0080] Table 4 The settings of each treatment group in Example 4
[0081] Group Modification temperature / ℃ Modification time / min Amount of stearic acid / % Processing 14 90 60 3.0 Processing 15 92 50 3.5 Processing 16 95 30 4.0
[0082] Comparative Example 1
[0083] Commercially available nano zinc oxide products.
[0084] Comparative Example 2
[0085] The core-shell structure nano material of zinc oxide coated calcium carbonate prepared by CN 111606351B.
[0086] Comparative Example 3
[0087] Nano zinc oxide / calcium carbonate composite powder prepared by CN113000058A.
[0088] 1. Product performance test experiment
[0089] 1. The zinc oxide particle size, composite powder whiteness and dispersibility of the CaCO3@ZnO core-shell structure composite powders prepared in treatments 1 to 16 and the products of comparative examples 1 to 3 were measured according to the following methods.
[0090] The dispersibility of the composite powder is judged by observing the scanning electron microscope image. The more clustered the calcium carbonate particles are, the worse the dispersibility is, and vice versa. Similarly, no less than 50 zinc oxide particles are selected in the scanning electron microscope image for point measurement, and finally the average value is taken to obtain the particle size of zinc oxide.
[0091] The CaCO3@ZnO core-shell structure composite powders prepared by treatments 1 to 16 and the products of comparative examples 1 to 3 were tested for whiteness using a whiteness meter.
[0092] 2. The measurement results are shown in Table 5.
[0093] Table 5 Performance of products obtained by each treatment
[0094] Group Zinc oxide coating amount / % Zinc oxide particle size / nm Composite powder whiteness Dispersibility Process 1 5 15~20 95.1 generally Process 2 10 15~20 95.2 generally Process 3 15 15~20 95.3 generally Process 4 15 15~20 95.4 Difference Process 5 5 15~20 95.0 Difference Process 6 5 10~15 95.5 good Process 7 10 10~15 95.6 good Process 8 15 10~15 95.7 good Process 9 5 10~15 95.3 generally Processing 10 15 25~35 95.6 generally Process 11 5 15~20 95.1 generally Processing 12 10 15~20 95.2 generally Process 13 15 15~20 95.3 generally Processing 14 5 10~15 95.5 good Processing 15 10 10~15 95.6 good Processing 16 15 10~15 95.7 good Comparative Example 1 100 25~35 95.5 Difference Comparative Example 2 10 15~20 95.3 generally Comparative Example 3 10 15~20 95.2 generally
[0095] Note: "Zinc oxide coating amount" refers to the percentage of the weight of zinc oxide in the composite powder to the weight of nano-calcium carbonate.
[0096] From Table 5 and the SEM images, we can see that:
[0097] (1) Fig.12 The figure shows a scanning electron microscope image of commercially available nano zinc oxide with a particle size of 25 to 35 nm. Due to the small particle size and large surface energy, the zinc oxide particles adhere to each other to form clusters, and the dispersion is poor. Under the process conditions of the present invention, soluble zinc salts and soluble carbonates are added when the pH value of the carbonation reaction system is 8.0 to 9.0 in treatments 1 to 3. The composite powder prepared has a zinc oxide content of 5% to 15% of the weight of nano calcium carbonate, a small specific gravity, and a whiteness of more than 95.1, which is equivalent to the whiteness of the pure nano zinc oxide product of Comparative Example 1. The generated zinc oxide is deposited on the surface of calcium carbonate in the form of particles, and the distribution is uneven, and no complete coating layer is formed ( Figures 1 to 3 ), and part of the zinc oxide is adsorbed on the surface of calcium carbonate in the form of independent nuclei, and the coating effect is similar to that of comparative example 3 ( Fig.13 ) are similar to the nano zinc oxide / calcium carbonate composite powders prepared by treatment 4 and treatment 5; however, in treatment 4 and treatment 5, the addition of zinc salt and carbonate too early or too late will lead to the poor dispersibility of CaCO3@ZnO core-shell structure composite powders ( Figure 4 and Figure 5 ), this is because, if it is added too early, the linear intermediates will not grow large enough to break before coating, and cubic or spherical nano-calcium carbonate cannot be formed, and the composite powder will form clusters; if it is added too late, the linear intermediates will break, and the broken nano-calcium carbonate will agglomerate due to the high surface energy, affecting the coating effect.
[0098] (2) Treatments 6 to 8 used a pH regulator to control the pH of the system. Compared with treatments 1 to 3, the ZnCO3 particle size was smaller and more evenly coated on the surface of the nano-calcium carbonate. The product had higher whiteness and better dispersibility ( Figures 6 to 8 The pH value of the control system has a great influence on the performance of the CaCO3@ZnO core-shell composite powder. If the pH value of treatment 9 is too low, calcium carbonate will react with acid, causing calcium carbonate to be corroded and dissolved ( Fig. 9 ); If the pH value of treatment 10 is too high, the particle size of the generated zinc oxide will increase, affecting the use effect ( Fig.10 ), this is because the basic properties of zinc oxide mainly include particle specific surface area and structure, which have a great influence on the rubber processing process. The activation effect of zinc oxide on the vulcanization system mainly depends on its specific surface area, that is, the smaller the particle size, the larger the specific surface area, and the better the activation effect.
[0099] 2. Product application effect test experiment
[0100] The products of each treatment group and comparative examples 1 to 3 were mixed in an open mill for about 30 min according to the formulation in Table 6, and the vulcanization characteristics of the rubber at 160°C were determined using an MDR-2000 vulcanizer according to GB / T9869-1997, and the tensile strength, elongation at break, tear strength and other mechanical properties were tested according to standard GB / T528-2009.
[0101] Table 6 Formulation of rubber application experiment
[0102]
[0103]
[0104] Table 7 Vulcanization data of various products used in styrene-butadiene rubber
[0105] Group <![CDATA[M H (N·m)]]> <![CDATA[M L (N·m)]]> <![CDATA[t 10 (min)]]> <![CDATA[t 90 (min)]]> Process 1 0.602 0.083 8.450 18.935 Process 2 0.641 0.082 8.669 17.587 Process 3 0.663 0.081 8.870 16.671 Process 4 0.652 0.084 8.791 17.144 Process 5 0.591 0.081 8.137 19.170 Process 6 0.682 0.083 8.850 17.128 Process 7 0.714 0.084 9.170 16.228 Process 8 0.742 0.086 9.337 15.473 Process 9 0.675 0.084 8.713 17.583 Processing 10 0.716 0.081 9.125 16.057 Process 11 0.625 0.081 9.035 17.983 Processing 12 0.658 0.084 9.087 16.657 Process 13 0.679 0.082 9.210 16.076 Processing 14 0.705 0.082 9.105 16.131 Processing 15 0.735 0.083 9.457 14.868 Processing 16 0.768 0.082 9.627 14.133 Comparative Example 1 0.711 0.084 9.133 14.931 Comparative Example 2 0.648 0.082 8.701 17.398 Comparative Example 3 0.633 0.083 8.479 18.004
[0106] Table 8 Mechanical properties of each product used in styrene-butadiene rubber
[0107]
[0108]
[0109] Nano zinc oxide is used as a rubber vulcanization accelerator to promote the vulcanization of rubber, and it plays an important role in rubber applications. As shown in Tables 7 and 8, when the CaCO3@ZnO core-shell structure composite powders prepared by treatments 1 to 3 are used in styrene-butadiene rubber, the mechanical properties and vulcanization properties of the rubber improve with the increase of ZnO content, which is specifically manifested in the scorch time (t 10 ) increases, the curing time (t 90 ) shortened, torque (M H -M L ) increases, the tensile strength, elongation at break and tear strength of the rubber are all improved. At the same content, the more uniform the zinc oxide distribution on the surface of nano-calcium carbonate, the better the coating effect, and the more superior the vulcanization performance and mechanical properties of the rubber (treatments 6 to 8).
[0110] The particle size of zinc oxide and the dispersibility of the CaCO3@ZnO core-shell structure composite powder also affect its application performance in rubber. For example, the CaCO3@ZnO core-shell structure composite powder prepared in treatment 10 has general dispersibility and a larger zinc oxide particle size, and its application effect is worse than that of treatment 8. Similarly, the dispersion of the CaCO3@ZnO core-shell structure composite powder in the rubber matrix and its compatibility with the rubber matrix also affect its application effect. The application effect of the CaCO3@ZnO core-shell structure composite powder modified with stearic acid in treatments 11 to 13 and 14 to 16 is better than that of the unmodified CaCO3@ZnO core-shell structure composite powder in treatments 1 to 3 and 6 to 8. This is because stearic acid modification can reduce the interaction between particles and the adhesion between polymers, so that the CaCO3@ZnO core-shell structure composite powder can be well dispersed when filled in the rubber. After surface modification with stearic acid, the hydrophilicity of the CaCO3@ZnO core-shell structure composite powder is eliminated, greatly increasing its compatibility with the rubber matrix.
[0111] It can also be seen from the data in the table that under the same coating amount, the CaCO3@ZnO core-shell structure composite powder (treatment 7) prepared by the method of the present invention has better performance than the CaCO3@ZnO core-shell structure composite powder prepared by patent CN 111606351B (comparative example 2) and patent CN113000058A (comparative example 3). In addition, when the content of zinc oxide in the product of the present invention is 10% of the weight of nano calcium carbonate, its application effect is better than commercially available nano zinc oxide.
[0112] The above results show that the CaCO3@ZnO core-shell structure composite powder prepared by combining carbonation method with precipitation method has good dispersibility and high whiteness. After modification with stearic acid, when the ZnO content in the core-shell structure composite powder is 10-15% of the weight of nano-calcium carbonate, it can replace nano-zinc oxide in rubber and have better performance.
[0113] The above contents are further detailed descriptions of the present invention in combination with specific / preferred implementations, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, they can also make several substitutions or modifications to these described embodiments without departing from the concept of the present invention, and these substitutions or modifications should be regarded as belonging to the protection scope of the present invention.
Claims
1. A CaCO3@ZnO core-shell structure composite powder, characterized in that: The core-shell structure composite powder comprises a nano calcium carbonate core and a zinc oxide shell coated on the surface of the core-shell structure composite powder. In the core-shell structure composite powder, the weight of zinc oxide is 5% to 15% of the weight of the nano calcium carbonate.
2. The CaCO3@ZnO core-shell structure composite powder as claimed in claim 1, characterized in that: In the core-shell structure composite powder, zinc oxide is deposited on the surface of calcium carbonate in the form of particles, and the particle size is 10-20 nm.
3. The CaCO3@ZnO core-shell structure composite powder according to claim 1, characterized in that: The core-shell structure composite powder further contains stearic acid, and the stearic acid is coated on the outer surface of the core-shell structure composite powder.
4. The method for preparing the CaCO3@ZnO core-shell structure composite powder according to claim 1 or 2, characterized in that: The following steps are involved: (1) preparing a calcium hydroxide slurry, and then introducing a mixed gas containing carbon dioxide into the slurry to cause a carbonation reaction. When the pH value of the system is 8.0 to 9.0, adding a soluble zinc salt and a soluble carbonate into the system, stirring and reacting, and obtaining a mixed slurry; (2) removing impurities and moisture from the mixed slurry obtained in step (1) to obtain CaCO3@ZnCO3 powder; (3) The CaCO3@ZnCO3 powder obtained in step (2) is calcined to obtain a CaCO3@ZnO core-shell structure composite powder.
5. The method for preparing the CaCO3@ZnO core-shell structure composite powder according to claim 4, characterized in that: In step (1), the solid content of calcium hydroxide in the calcium hydroxide slurry is 8.0-15.0%.
6. The method for preparing the CaCO3@ZnO core-shell structure composite powder according to claim 4, characterized in that: In step (1), the temperature of the carbonation reaction is 18-25°C.
7. The method for preparing the CaCO3@ZnO core-shell structure composite powder according to claim 4, characterized in that: In step (1), the soluble zinc salt is one of zinc acetate dihydrate, zinc citrate, zinc chloride, zinc sulfate, and zinc nitrate; and the soluble carbonate is one of sodium carbonate, potassium carbonate, ammonium carbonate, and ammonium bicarbonate.
8. The method for preparing the CaCO3@ZnO core-shell structure composite powder according to claim 4, characterized in that: In step (1), the pH value of the system is regulated to be 7.0-8.5 during the stirring process.
9. The method for preparing the CaCO3@ZnO core-shell structure composite powder according to claim 4, characterized in that: In step (3), the heating rate of calcination is 3-10°C / min, and the temperature is raised to 300-450°C and then kept at this temperature for 1-5 hours.
10. The method for preparing the CaCO3@ZnO core-shell structure composite powder according to any one of claims 4 to 9, characterized in that: In step (3), the surface of the CaCO3@ZnO core-shell structure powder is modified by using stearic acid as a modifier, the amount of stearic acid used is 3.0-4.0% of the weight of the nano calcium carbonate; the modification temperature is 90-95°C, and the time is 30-60 minutes.
Citation Information
Patent Citations
Industrialized preparation of nano-calcium carbonate for antibacterial fungistatic silicon rubber
CN101412818A
Core-shell zinc oxide powder and ammonia type preparation method thereof
CN106279762A
High-brightness, anti-ultraviolet and anti-aging functional filler nano-calcium carbonate and its preparation method and use
CN106752106B
A zinc oxide-coated calcium carbonate nanomaterial and its preparation method
CN111606351B
Preparation method and application of nano zinc oxide / calcium carbonate composite powder
CN113000058A